From invisible to tangible power in Late Antique rural Lusitania: between text and material evidence - Carneiro, André (2021)
This paper analyses the evolution in the territory of Augusta Emerita (Mérida), the capital of Lusitania Province, seeking to contrast the archaeological information related to the new occupation profiles of the sites, uilla life and changes in ownership, with the perception conveyed by the Vitas Sanctorum Patrum Emeritensium on this specific phenomenon, in order to contribute to the understanding of the local context and its dynamics in Lusitania after the collapse of the Empire.